PENGOLAHAN COOKIES BERBAHAN PISANG PADA KELOMPOK JALAPAGOS DI DESA BUON MANDIRI KECAMATAN LUWUK UTARA KABUPATEN BANGGAI SULAWESI TENGAH - Ramadhani Chaniago; Haruni Ode; Rahman Dani Lasamadi; Darni Lamusu (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Utilization of bananas so far has not been optimal, it is still limited to consumption and traditional processed fruit. Various types of snacks from bananas that are relatively popular include banana chips, banana sale, banana molen and cookies. Cookies are one type of snack that people are interested in. Cookies are known by many people, both children, teenagers and adults, who live in rural and urban areas. Cookies are cakes made from flour which are generally made from flour, powdered sugar, chicken eggs, vanilla, margarine, cornstarch, baking powder, and instant milk powder. The implementation of activities includes the preparation and implementation stages in the form of training and manufacturing practices. After the implementation of the cookie-making training activities, they can increase the knowledge and skills of the Jalapagos group mothers about the potential of banana plants and can realize the economic independence of the community in Buon Mandiri Village, North Luwuk District, Banggai Regency